2022
DOI: 10.3389/fcomm.2022.874215
|View full text |Cite
|
Sign up to set email alerts
|

Face-Masked Speech Intelligibility: The Influence of Speaking Style, Visual Information, and Background Noise

Abstract: The current study investigates the intelligibility of face-masked speech while manipulating speaking style, presence of visual information about the speaker, and level of background noise. Speakers produced sentences while in both face-masked and non-face-masked conditions in clear and casual speaking styles. Two online experiments presented the sentences to listeners in multi-talker babble at different signal-to-noise ratios: −6 dB SNR and −3 dB SNR. Listeners completed a word identification task accompanied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 59 publications
2
3
0
Order By: Relevance
“…Further researchers examined this effect in a positive-emotional speech in multi-talker babble (Cohn, 2021). Similar to Pycha and colleagues’ (2022) findings, listeners’ intelligibility was not affected by a fabric face mask during clear speech; however, intelligibility was affected by the presence of a face mask in casual speech. The authors suggested that “emotional” and “casual” speech styles are not produced with the intent to be intelligible to listeners; therefore, the presence of a face mask would further hinder a listener’s speech intelligibility.…”
Section: Face Maskssupporting
confidence: 82%
See 2 more Smart Citations
“…Further researchers examined this effect in a positive-emotional speech in multi-talker babble (Cohn, 2021). Similar to Pycha and colleagues’ (2022) findings, listeners’ intelligibility was not affected by a fabric face mask during clear speech; however, intelligibility was affected by the presence of a face mask in casual speech. The authors suggested that “emotional” and “casual” speech styles are not produced with the intent to be intelligible to listeners; therefore, the presence of a face mask would further hinder a listener’s speech intelligibility.…”
Section: Face Maskssupporting
confidence: 82%
“…Research conducted by Smiljanic and colleagues (2021) further examined this effect with native- and non-native speakers. The results were similar to Pycha and colleagues (2022) in that listeners were as accurate in a masked word recognition task as they were under an unmasked condition in optimal listening conditions (i.e., clear speech presented under quiet listening conditions). Masks tended to affect non-native speech processing at easier noise levels.…”
Section: Face Maskssupporting
confidence: 80%
See 1 more Smart Citation
“…Similar studies on globally accented speech and speaker guises (e.g. Rubin 1992, Yi et al 2013, Babel & Russell 2015, McGowan 2015, Pycha et al 2022 all point to a similar conclusion, namely, that guises affect listeners' overall interpretation of the speech signal.…”
Section: 2mentioning
confidence: 72%
“…Therefore, the present results are in line with those obtained by Singh et al (2021) , who also found no differences in terms of word-object identification between speech with mask or without mask. As some researchers have claimed ( Pycha et al, 2022 ; Wermelinger et al, 2022 ), speakers might modify their language production in the presence of a physical barrier, namely a face mask, in order to make their speech more intelligible. In fact, previous findings have already shown that speakers tend to increase their speech quality (i.e., speech rate, pitch, length of words, etc.)…”
Section: Discussionmentioning
confidence: 99%